Career Progression of Female Accountants in the State Public Sector - Cullen, Lisa; Christopher, T. (Wiley-Blackwell Publishing Asia, 2012)
This study investigated the relationship of career anchors and work-related barriers to career progression for female CPA members working in the New South Wales (NSW) and Western Australian (WA) state public sector. Results of regression analysis found technical functional competence, managerial competence, security and pure challenge career anchors to be significant and related to career progression in WA. Additionally the security and lifestyle career anchors were significant in NSW. Work-related barriers were found to be significant and negatively related to career progression. These findings suggest alternative strategies to improve career outcomes for women working in the state public sector.